A critical discourse analysis (CDA) of a political speech of Mr. Christian Tadele speech in the parliament - Yitbarek Mekt; Animut Getahun; Tarik Meseret (Journal of Education, Social & Communication Studies, 2024)
This paper presents a Critical Discourse Analysis (CDA) of a political speech delivered by Mr. Christian Tadele in the Ethiopian parliament. The study aims to uncover hidden ideologies, future agendas, and linguistic components in Mr. Tadele's speech through the examination of strategies such as politeness and inclusive language, as well as the analysis of frequently used words like "we," "democracy," and "corruption." By applying Fairclough's 3D Model, the analysis focuses on the social context and the use of language within institutional and political discourses to reveal potential inequalities in social relationships. The research also explores the impact of the speech on the public, particularly the supporters of Mr. Tadele's political party, and examines concepts related to rent-seeking and corruption. The significance of the study lies in its contribution to uncovering concealed ideologies, raising awareness among both producers and consumers of political discourse, and providing new insights to readers.